EXILE AND COSMOPOLITANISM IN PLUTARCH’S POLITICAL AND PHILOSOPHICAL THOUGHT - De Simone, Pia (Prometheus - Journal of Philosophy., 2020)
Plutarch plays a distinctive role within Greek universalism in the Hellenistic age, as he has dealt with the theme of cosmopolitanism in numerous writings of a different nature (historical, philosophical, political and literary) and animated by multiple purposes. The aim of this paper is to focus on Plutarch’s view on cosmopolitanism which emerges from his treatise De exilio, an emblematic writing, as it allows recognizing that in Plutarch cosmopolitanism is not a merely political issue, but rather it reflects ethical and metaphysical concerns.